2016
DOI: 10.1002/adfm.201601902
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus‐Doped Perovskite Oxide as Highly Efficient Water Oxidation Electrocatalyst in Alkaline Solution

Abstract: 1 wileyonlinelibrary.com evolution reaction (OER) is currently the limiting factor on the water splitting due to its sluggish kinetics involving the complex four-electron oxidation process. [3] To this end, the presence of an efficient OER electrocatalyst is essential to obtain an accelerated reaction rate. At present, precious metal-based iridium and ruthenium oxides (i.e., IrO 2 and RuO 2 ) are regarded as the OER catalysts benchmarks, [4] but their scarcity and high cost have hindered their wide-scale appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
225
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 310 publications
(240 citation statements)
references
References 83 publications
12
225
0
3
Order By: Relevance
“…X-ray photo electron spectroscopy, X-ray absorption near-edge structure, and extended X-ray absorption fine structure experiments demonstrate that the superior performance is due to the strong electronic interaction between Pt and SCFP that arises as a result of the rapid electron transfer via the PtOCo bonds as well as the higher concentration of surface oxygen vacancies. [14] Building on this previous work, here we synthesized the Fe-doped analogue of the SCP, Sr(Co 0.8 Fe 0.2 ) 0.95 P 0.05 O 3−δ (SCFP), via solid-state reaction route. Undoubtedly, this work provides an efficient approach for developing low-cost and highly active catalysts for wider application of electrochemical energy devices.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray photo electron spectroscopy, X-ray absorption near-edge structure, and extended X-ray absorption fine structure experiments demonstrate that the superior performance is due to the strong electronic interaction between Pt and SCFP that arises as a result of the rapid electron transfer via the PtOCo bonds as well as the higher concentration of surface oxygen vacancies. [14] Building on this previous work, here we synthesized the Fe-doped analogue of the SCP, Sr(Co 0.8 Fe 0.2 ) 0.95 P 0.05 O 3−δ (SCFP), via solid-state reaction route. Undoubtedly, this work provides an efficient approach for developing low-cost and highly active catalysts for wider application of electrochemical energy devices.…”
Section: Introductionmentioning
confidence: 99%
“…Even at ah igh power delivery rate (6600 Wkg À1 ), the hybrid cell maintains ah igh energy density (33 Wh kg À1 )w ith ac harging time of only 20.7 s. To our knowledge, no pior study has demonstrated the charge storage characteristics of SCM for supercapacitort echnologies. [31] The deconvoluted spectrum of Co ( Figure 1d)s uggests the presence of cobalt in two oxidation states,n amely Co 2 + and Co 3 + .F rom the core level spectrum, two major peaks observed around 781 and 779.6 eV are attributed to Co 2 + and Co 3 + 2p 3/2 ,r espectively. [24] In contrast, all the diffraction peaks of SC matched with the hexagonal phase ( Figure S1 ai nt he Supporting Information) [36] of strontium cobaltite.…”
Section: Introductionmentioning
confidence: 99%
“…So far, donor or electron doping of highly charged cations into SrCoO 3− δ have been widely employed as effective way to enhance the electrical conductivity. For example, Zhu et al reported that P 5+ doped SrCo 0.95 P 0.05 O 3− δ perovskite exhibits a stable tetragonal structure and features much higher electrical conductivity relative to SC, thus displaying improved OER activity 13a. Some other highly charged cations (e.g., Nb 5+ , Ta 5+ , Sc 3+ , Ti 4+ ) was also used to stabilize the Co sites in SC, but these doped cations themselves are inert to OER, which will not help further activity enhancement to some extent.…”
mentioning
confidence: 99%